Pre-operative physiotherapy following unilateral ankle fractures at a tertiary hospital in South Africa: Perceptions of patients and nurses - Sabeeha Dangor; Prithi Jayaraman-Pillay; Stacy Maddocks; Verusia Chetty (AOSIS, 2021)
Background: Ankle fractures are a common injury because of an increase in levels of physical activity, as well as senescence worldwide. Ankle fractures often require surgical management for optimal stabilisation. Pre-operative physiotherapy is necessary to prepare patients for early mobilisation and home discharge. There is a lack of information on the influence of pre-operative physiotherapy on post-operative rehabilitation success, as well as timeous discharge, in patients with ankle fractures. Objectives: To explore the perceptions of patients receiving pre-operative physiotherapy care following a unilateral ankle fracture and the perceptions of nursing staff managing these patients at a tertiary hospital in South Africa. Method: A descriptive qualitative design, using semi-structured interviews, including both patients with unilateral ankle fractures and nurses caring for these patients, was adopted. Interviews were recorded and verbatim transcriptions were analysed utilising thematic analysis. Results: Four overarching themes emerged: the perceived benefits of pre-operative physiotherapy; inhibitors to physiotherapy rehabilitation; hidden enablers to pre-operative physiotherapy and future initiatives for rehabilitation. Conclusion: The perceived benefits included improved functional independence and safety of patients, as well as reduced burden of care for nurses. Patients also believed that pain and fear were two inhibitors to physiotherapy. Furthermore, nurses identified that organisational limitations, such as short-staffing and inadequately trained staff, inhibited pre-operative physiotherapy and continuity of care. Early post-operative discharge was a crucial hidden enabler to the pre-operative physiotherapy protocol. Recommendations included improved health education; the potential role of nursing staff as facilitators in pre-operative rehabilitation and regular, pre-operative in-patient monitoring of physiotherapy intervention. Clinical implications: Health education was perceived to have improved patient safety and compliance which subsequently reduced patient safety incidences as well as served as a risk mitigation measure. Furthermore, gait training and muscle strengthening exercises was perceived to have resulted in safe, independent mobility to ensure prompt discharge home. Consequently, a reduced post-operative length of in hospital stay results in major cost savings per patient as well as improved access and bed availability. Future studies may need to explore the effects of pre-operative physiotherapy on post-operative success and return to pre-injury activity.